Bridging the Gap Between Curriculum, Innovative Pedagogy, and Evolving Industry Demands for Future-Ready Graduates - Judith Nkolika, Chukwuka (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The increasing disconnect between academic curricula and industry demands presents a major challenge in preparing graduates for the evolving workforce. This study examines the extent to which tertiary institutions in Anambra State, Nigeria, align their curricula with industry expectations, integrate innovative pedagogical approaches, and foster academia-industry collaboration to enhance graduate employability. A descriptive survey research design was adopted, involving 61 respondents drawn from academic staff, curriculum developers, and industry professionals. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistical methods, including the Mann-Whitney U test and Spearman’s rho correlation analysis. Findings reveal significant gaps between current educational curricula and industry needs, limited integration of employer perspectives, and inadequate practical skill development. While innovative pedagogical approaches were identified as essential for producing industry-ready graduates, their implementation remains inconsistent across institutions. Similarly, academia-industry collaboration, including internship opportunities and research partnerships, was found to be weak, particularly in state institutions. The study pointed out the need for regular curriculum updates, increased technology integration in teaching. It recommends policy reforms, structured internship programs, and investment in skill-based learning as essential strategies for bridging the gap between academic training and labor market expectations. Keywords: Curriculum alignment, innovative pedagogy, academia-industry collaboration, graduate employability, industry demands.